PENTINGNYA MENGENALKAN KERAGAMAN BUDAYA DI SEKOLAH DASAR - Saputra, Ariya; Sabrina, Dinda Nila; Wijayanti, Isnaeni; Setiyoko, Didik Tri (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This research aims to highlight the urgency of introducing cultural diversity to elementary school students as an effort to build inclusive character and strengthen a sense of nationalism. Cultural diversity is one of Indonesia's main riches that needs to be introduced to the younger generation from an early age. This research uses a literature review method which focuses on analyzing appropriate literature. This article was obtained from several sources, for example Google Scholer, Garuda, and Sinta. The introduction of cultural diversity not only contributes to the formation of mutual respect, but also minimizes stereotypes and prejudice. Through a creative and integrated approach to the curriculum, students can learn to understand, appreciate and celebrate the richness of Indonesian culture. The results of this research show that it is important to apply cultural diversity to elementary school children so that they are accustomed to different cultures in each place or region and is an important step in creating a learning environment that can provide in-depth understanding. This research itself discusses the importance of introducing cultural diversity in elementary schools.